Indonesian Curriculum Development: Meaning-Based Curriculum and Competency-Based Curriculum in the Context of Teaching English Subject - . Subandi (Bandar Lampung University (UBL), 2014)
Curriculum as the foundation of teaching and learning process coverssubject matters and students’ learning experience frominside and outside of school. This articleaims at describing Indonesian curriculum developments, which consist of Meaning-Based Curriculum (MBC) and Competency-Based Curriculum (CBC), basedon theoretical dimension and practical dimension. Curriculum views as a theoretical dimension are underpinned by four models of curriculums that consist of (1) dualistic model, (2) interlocking model, (3) concentric model, (4) cyclical model. Meanwhile, English subject matter curriculum (ESMC) views as a practical dimension are based upon (1) thematic development inMBC, (2) syllabus development in CBC. Two theoretical dimensions of the Indonesian curriculum views describe (1) Concentric model is incorporated into MBC in the 1994 Curriculum and CBC in the 2004 and 2013 Curriculum; (2) Interlocking model is incorporated intoCBC in the 2006 Curriculum. Three dimensions of ESMC views describe (1) Thematic development is incorporated into MBC in the 1994 Curriculum to develop students’ English skills and components based on selected themes, (2) Syllabus development is incorporated intoCBC to develop students’ English competences by the 2004 and 2006 Curriculum; however, in the 2013 Curriculum to develop students’ core competences for character values that are attached in science and technology by Exploring English without adequately equipping students with English skills and components.